Exosome microRNA signatures in patients with complex regional pain syndrome undergoing plasma exchange - Ramanathan, Sujay; Douglas, Sabrina R.; Alexander, Guillermo M.; Shenoda, Botros B.; Barrett, James E.; Aradillas, Enrique; Sacan, Ahmet; Ajit, Seena K. (Journal of translational medicine, 2019)
Background Therapeutic plasma exchange (PE) or plasmapheresis is an extracorporeal procedure employed to treat immunological disorders. Exosomes, nanosized vesicles of endosomal origin, mediate intercellular communication by transferring cargo proteins and nucleic acids and regulate many pathophysiological processes. Exosomal miRNAs are potential biomarkers due to their stability and dysregulation in diseases including complex regional pain syndrome (CRPS), a chronic pain disorder with persistent inflammation. A previous study showed that a subset of CRPS patients responded to PE. Methods As a proof-of-concept, we investigated the PE-induced exosomal miRNA changes in six CRPS patients. Plasma cytokine levels were measured by HPLC and correlated with miRNA expression. Luciferase assay following co-transfection of HEK293 cells with target 3′UTR constructs and miRNA mimics was used to evaluate miRNA mediated gene regulation of target mRNA. Transient transfection of THP-1 cells with miRNA mimics followed by estimation of target gene and protein expression was used to validate the findings. Results Comparison of miRNAs in exosomes from the serum of three responders and three poor-responders showed that 17 miRNAs differed significantly before and after therapy. Of these, poor responders had lower exosomal hsa-miR-338-5p. We show that miR-338-5p can bind to the interleukin 6 (IL-6) 3′ untranslated region and can regulate IL-6 mRNA and protein levels in vitro. PE resulted in a significant reduction of IL-6 in CRPS patients. Conclusions We propose that lower pretreatment levels of miR-338-5p in poor responders are linked to IL-6 levels and inflammation in CRPS. Our data suggests the feasibility of exploring exosomal miRNAs as a strategy in patient stratification for maximizing therapeutic outcome of PE.